Nutritional value and seasonal availability of feed ingredients for pigs in Uganda - Carter, Natalie A.; Dewey, Catherine E.; Lukuyu, Ben A.; Grace, Delia; Lange, C.F.M. de (Walter de Gruyter GmbH, 2015)
In this study nutritional values and seasonal availability of 43 local feed ingredients for pigs in Uganda, were estimated based on nutrient analyses and literature values, information needed to develop low-cost balanced rations for pigs on smallholder farms. Parameters considered were: concentration of ash, neutral detergent fibre (NDF), crude protein (CP), calcium (Ca), phosphorous (P), ether extract (EE), total lysine (Lys), standardized ileal digestible (SID) Lys, standardized total tract digestible (STTD) P (all as % of dry matter [DM]); digestible energy (DE), (kcal kg−1 of DM); and DM concentration. Concentration of DE, total Lys, SID Lys, and STTD P were estimated. Ingredient seasonal availability and relative importance were identified. Ground sun-dried fish (Rastrineobola argentea) had highest estimated DE concentration and Napier grass (Pennisetum purpureum) had lowest (4209 and 535 kcal kg−1 of DM, respectively). Ground sun-dried fish had highest CP and estimated total Lys concentration (59.9 and 6.7% of DM, respectively) and banana peel (Musa sapientum), had lowest (5.21 and 0.08% of DM, respectively). Milled ingredients sampled here had higher ash than in the literature (e.g. ground sun-dried fish 58.1 vs 15.9% of DM) likely indicating sand contamination. There were 3 seasons of availability of ingredients. Banana peel, maize bran, and sweet potato vine (Ipomoea batatas) were ranked highest; and commercially-prepared ration, and kale/collard greens (Brassica oleracea var. acephala), were ranked lowest as potential feed ingredients. Ingredients with nutritional profiles suitable for pigs are available but some only in certain seasons. Estimated nutritional values may assist in ration formulation.